Soft-computing-based nonlinear control systems design - Singh, Uday Pratap, 1979 February 06-; Tiwari, Akhilesh, 1982-; Singh, Rajeev Kumar, 1986- (IGI Global, 2018)
"This book focuses on new developments and contributions in the areas of soft computing which are related to optimization, control and automation. It covers how the global soft-computing based techniques are used for global optimization problems of decision-making, supply chain management, power and control optimization, nuclear energy, space exploration, bio-medical and health care, pattern recognition image processing"-- Provided by publisher.
Keywords: Automatic control.; Nonlinear control theory.; Soft computing.; elektronické knihy; electronic books